Determinan Akuntabilitas Pengelolan Dana Desa: Studi Kasus Aparat Pemerintah Kecamatan Semarang Barat - Novita Puspita Shanti; M G Kentris Indarti (Jurnal Ilmiah Akuntansi dan Humanika, 2021)
This study was conducted to determine the factors that affect the accountability of village fund management. Village administration officials in West Semarang District stated that the accountability of village fund management in West Semarang District was still not optimal. Lack of village apparatus competence or human resource competence is the cause of the problem of not achieving village fund management accountability. The village administration of West Semarang Sub-district is still unable to utilize village funds optimally, resulting in delays in the disbursement of village funds the following year. In addition, administrative errors that caused delays in the disbursement of village funds were also caused by village officials in the West Semarang District, who on average graduated from high school and were old. The instrument of study is in the from quesioners. The population in this study is the village officials in the west semarang district. The sampling technique this study used a purpopsive sampling method with 70 respondens and analyzed by multiple linear regression. The results of the study indicate that the variabel village officials competence, commitment of village government organizations, internal control systems have a significant positive effect the village fund management accountability.